Regional integration and internal economic geography: an empirical evaluation with Portuguese data - Crespo, N.; Fontoura, M. P. (Regional and Sectoral Economic Studies, 2013)
he effects of the reduction of international trade costs on the internal economic geography of a country have been very scarcely studied in empirical terms. With data for Portugal since its adhesion to the European Union, we analyze the hypotheses put forward by the new economic geography concerning the evolution of the spatial concentration of the manufacturing industry as a whole and of each individual sector. We use four alternative concentration concepts and data disaggregated both at the level of NUTS III (28 regions) and concelhos (275 regions). Results show a dispersion of manufacturing industry, in line with Krugman and Elizondo's (1996) prediction. Individual sectors show a similar tendency, in contrast with the theoretical hypothesis.